Long-term anti-SARS-CoV-2 antibody trajectories after neutralizing monoclonal antibody treatment. - Elizabeth S Munroe; Greg A Grandits; Robert C Hyzy; Hallie C Prescott; Thomas W Barrett; Robin L Dewar; Nicole Engen; Anna L Goodman; Timothy J Hatlen; Helene Highbarger; Thomas L Holland; Gareth Hughes; et al. (PLoS ONE)
Background Neutralizing monoclonal antibodies (nMAbs) have been used to treat COVID-19 and are increasingly being used to treat other infections. However, there is concern that by neutralizing the SARS-CoV-2 virus, nMAbs may decrease the availability of antigens to the immune system, potentially impairing the endogenous polyclonal immune response and decreasing long-term immune protection. Methods We compared 28 and 90-day anti-SARS-CoV-2 spike protein neutralization activity and anti-SARS-CoV-2 nucleocapsid response for patients hospitalized with COVID-19 infection randomized to receive nMAbs or placebo in the large platform ACTIV-3/TICO trials. We pooled results from four trials of anti-spike nMAbs. For most tested agents, measurements of the spike protein response reflect both the therapeutic and endogenous immune response. Anti-nucleocapsid levels reflect only the endogenous immune response. Data are summarized as mean differences in percent binding inhibition (anti-spike) and signal-to-cutoff (S/C) ratio (anti-nucleocapsid). Linear mixed effects models were fit to compare the longitudinal trajectory between treatment and placebo groups. Results Of 2,254 participants in the ACTIV-3/TICO trials modified intention-to-treat population, 2,149 (95.3%) had antibody measures at baseline and at least 1 follow-up day (day 1, 3, or 5) and were included in this analysis. Antibody measures were available for 1,556 (72.4%) participants at day 28 and 1,429 (66.5%) participants at day 90. In participants who received nMAbs, anti-spike neutralization activity was higher at day 28 (mean difference in percent binding inhibition: 7.1% [95%CI: 5.3, 8.9], p < 0.001) and day 90 (mean difference in percent binding inhibition: 7.2% [95% CI: 5.4, 9.0], p < 0.001). Anti-nucleocapsid response was similar at day 28 (mean difference in S/C ratio: 0.02 [95%CI: -0.11, 0.15], p = 0.75) and day 90 (mean difference in S/C ratio: 0.08 [95% CI: -0.05, 0.21], p = 0.22). Similar patterns were observed in all trials. Conclusions In patients hospitalized with COVID-19, treatment with nMAbs did not decrease long-term anti-nucleocapsid response compared to placebo, suggesting neutralizing therapies do not suppress the endogenous humoral immune response in this population.